Don't Be a Stiff: A Review Article on the Management of Tetanus. (January 2021) - Fields, Brentney; Guerin, Caitlin Sinclair; Justice, Stephanie Baker
Abstract : Vaccine-preventable diseases, such as tetanus, are oftentimes a thought of the past in countries that only see a handful of cases per year. In recent years, though, there has been more controversy around vaccinations and fewer individuals getting vaccinated. This movement has resulted in vaccine-preventable diseases resurfacing (e.g., measles). Tetanus is one of the diseases that health care providers should continue to be familiar with in regard to its clinical presentation and the treatments that are available to manage the corresponding signs and symptoms. Because tetanus is an acute, toxin-mediated illness that can be fatal, prevention and treatment are critical. This article briefly summarizes tetanus and the therapies considered to be first line in its management.